1987
DOI: 10.1139/x87-105
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nutrition of containerized Pinusresinosa at exponentially increasing nutrient additions

Abstract: Containerized red pine (Pinusresinosa Ait.) seedlings were reared on different fertility regimes that compared conventional applications of a recommended 39 mg N per seedling as a complete nutrient solution (175 mg N•L−1) with more frequent applications of an equal, one-half, or one-quarter amount of nutrients delivered at exponentially increasing solution concentrations over the same time period. Height growth, dry matter production, and root development at the end of the greenhouse rotation was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 0 publications
1
29
1
3
Order By: Relevance
“…Seedlings were rinsed in distilled water, separated at the root collar, composited by treatment-replicate, dried in an oven at 70 ºC for 48 hours, and weighed. Chemical analysis was then conducted according to methods described in Timmer and Armstrong [41]. Vector diagnosis [20] was used to examine temporal changes in growth and nutrient status during the hardening period as demonstrated with N using sequential sampling data.…”
Section: Sampling and Vector Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Seedlings were rinsed in distilled water, separated at the root collar, composited by treatment-replicate, dried in an oven at 70 ºC for 48 hours, and weighed. Chemical analysis was then conducted according to methods described in Timmer and Armstrong [41]. Vector diagnosis [20] was used to examine temporal changes in growth and nutrient status during the hardening period as demonstrated with N using sequential sampling data.…”
Section: Sampling and Vector Diagnosismentioning
confidence: 99%
“…Nutrient loading, or extra-high fertilization that builds up internal nutrient reserves during nursery culture, has been shown to improve outplanting performance of overwintered seedlings both in the field [30,32,42] and in pot trials [34,46] as the stored nutrients are retranslocated to growing apices during the initial flush of shoot expansion after transplanting when new root growth is restricted [41]. Nutrient loading before hardening may counter late-season dilution [39], although some growers are reluctant to adopt this practice because of concerns that high N fertilization may jeopardize frosthardiness development in seedlings prior to winter storage [2,17,43].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, supplying full-element solutions to plants in lower nutrient concentration but higher nutrient addition rate during the exponential growth phase may generally provide a better rationale to build steady-state nutrition in seedlings, which subsequently induces maximum plant growth (Ingestad and Lund 1986;Ingestad 1987;Timmer and Armstrong 1987;Zabek and Prescott 2007). Exponential rather than constant fertilizer addition can promote early root development and better match relative growth and nutrient consumption during the exponential growth phase of seedlings Imo and Timmer 1992;Xu and Timmer 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was concluded in some species such as Pinus resinosa Ait. (Timmer and Armstrong 1987), Picea mariana (Mill.) B.S.P.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is that of exponential fertilization, where the rate of fertilization is increased exponentially in concert with the exponential growth of the the tree seedling. In one such study (Timmer and Armstrong 1987b), the results indicated that superior seedlings can be produced at significantly lower fertilization levels than at conventional fertilization levels.…”
Section: Seedling Nutrition Studiesmentioning
confidence: 99%